Reduced Triacylglycerol Mobilization during Seed Germination and Early Seedling Growth in Arabidopsis Containing Nutritionally Important Polyunsaturated Fatty Acids - Shrestha, Pushkar; Callahan, Damien L.; Singh, Surinder P.; Petrie, James R.; Zhou, Xue-Rong (Frontiers in Plant Science, 2016)
There are now several examples of plant species engineered to synthesise and accumulate nutritionally important polyunsaturated fatty acids in their seed triacylglycerols (TAG). The utilization of such TAG in germinating seeds of such transgenic plants was unknown. In this study, we examined the TAG utilization efficiency during seed germination in transgenic Arabidopsis seeds containing several examples of these fatty acids. Seed TAG species with native fatty acids had higher utilization rate than the TAG species containing transgenically produced polyunsaturated fatty acids. Conversely, quantification of the fatty acid components remaining in the total TAG after early stages of seed germination revealed that the undigested TAGs tended to contain an elevated level of the engineered polyunsaturated fatty acids (PUFA). LC-MS analysis further revealed asymmetrical mobilization rates for the individual TAG species. TAGs which contained multiple PUFA fatty acids were mobilized slower than the species containing single PUFA. The mobilised engineered fatty acids were used in de novo membrane lipid synthesis during seedling development.